2001
DOI: 10.1046/j.1442-200x.2001.01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulopathy with mesangial IgM deposits: Long‐term follow up of 64 children

Abstract: Of IgM nephropathy patients with MCNS and DMH, a significant percentage develop impaired renal function, due to the evolution of FSGS, as revealed by repeat biopsy during long-term follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 23 publications
(66 reference statements)
3
31
1
7
Order By: Relevance
“…This pattern was also noted in one third of the cases in our study (Mubarak et al, 2011). Still other investigators have reported progression of IgMN cases with minor changes or mesangial proliferation into FSGS on repeat biopsies (Myllimaki et al, 2003;Zeis et al, 2001). We have observed one case each of florid crescentic GN and a case of collapsing FSGS as a morphologic expression of IgMN (unpublished data).…”
Section: Light Microscopysupporting
confidence: 83%
“…This pattern was also noted in one third of the cases in our study (Mubarak et al, 2011). Still other investigators have reported progression of IgMN cases with minor changes or mesangial proliferation into FSGS on repeat biopsies (Myllimaki et al, 2003;Zeis et al, 2001). We have observed one case each of florid crescentic GN and a case of collapsing FSGS as a morphologic expression of IgMN (unpublished data).…”
Section: Light Microscopysupporting
confidence: 83%
“…Some series, however, have shown that the presence of IgM is of prognostic significance. 9,10 Furthermore, recent reports suggest that rituximab, a mAb to CD20 that depletes mature B cells, may be beneficial in some patients with the nephrotic syndrome. [11][12][13][14][15][16] However, the mechanisms by which rituximab alleviates the nephrotic syndrome are not yet known.…”
mentioning
confidence: 99%
“…The disease, like IgA nephropathy (IgAN), is defined by its immunohistologic features: the presence of IgM as the sole or dominant immunoglobulin in the mesangial regions of the glomeruli in a diffuse (all glomeruli) and global (the entire glomerulus) distribution [4][5][6][7] . Its incidence varies, in accordance with different series, between 4.8% and 8.6% of all renal biopsies, affecting all ages and without predilection for gender [6,8,9,10] . Some authors report a higher frequency of glucocorticoidresistance or glucocorticoid-dependence with relatively few cases of complete remission [2,11,12] .…”
Section: Introductionmentioning
confidence: 57%